2023
DOI: 10.3389/fped.2023.1120459
|View full text |Cite
|
Sign up to set email alerts
|

Current and future methods of probiotic therapy for necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a complex intestinal disease that primarily affects premature neonates. Given its significant mortality and morbidity, there is an urgent need to develop improved prophylactic measures against the disease. One potential preventative strategy for NEC is the use of probiotics. Although there has been significant interest for decades in probiotics in neonatal care, no clear guidelines exist regarding which probiotic to use or for which patients, and no FDA-approved products exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…While the rationale for the use of probiotics is clear, the efficacy of enteral probiotics in preventing NEC in human neonates has been variable 76 . In fact, the American Association of Pediatrics has suggested that, at this stage, probiotics should not be routinely used to prevent NEC due to concerns of probiotic-related sepsis, contamination or poor manufacturing, and questionable effects in the preterm neonatal population, particularly those weighing < 1000 g 77 .…”
Section: Discussionmentioning
confidence: 99%
“…While the rationale for the use of probiotics is clear, the efficacy of enteral probiotics in preventing NEC in human neonates has been variable 76 . In fact, the American Association of Pediatrics has suggested that, at this stage, probiotics should not be routinely used to prevent NEC due to concerns of probiotic-related sepsis, contamination or poor manufacturing, and questionable effects in the preterm neonatal population, particularly those weighing < 1000 g 77 .…”
Section: Discussionmentioning
confidence: 99%